CBX3 regulated by miR-139 promotes the development of HCC by regulating cell cycle progression. Issue 16 (18th August 2022) - Zhang, Pan; Yang, Xiaoyan; Zha, Zhongming; Zhu, Yumeng; Zhang, Guoqiang; Li, Guotao
ABSTRACT: Hepatocellular carcinoma (HCC), a major primary liver cancer, is one of the most lethal malignancies worldwide. Increasing evidence has demonstrated that chromobox protein homolog 3 (CBX3) functions as an oncogene in different cancers. However, its expression profiles and biological functions in HCC remain unknown. Data on CBX3 expression in HCC acquired from the GEO and TCGA databases were analyzed. The biological functions of CBX3 in HCC were examined by in vitro experiments. Bioinformatics analysis, qRT-PCR and western blotting were performed to explore the mechanism of CBX3 in HCC. CBX3 mRNA was upregulated in HCC tissues, and overexpression of CBX3 mRNA was negatively correlated with malignancies and poor prognosis in HCC patients. CBX3 knockdown decreased growth, migration and invasion of HCC cells in vitro. Moreover, bioinformatics analysis and experimental observation indicated that CBX3 expression was correlated with cell cycle regulatory proteins in HCC cells. Finally, starBase predicted that miR-139 could directly target CBX3 in HCC. Confirmatory experiments verified that miR-139 overexpression attenuated HCC cell proliferation and migration, and these effects could be reversed by overexpressing CBX3. Our results showed that the miR-139/CBX3 axis may be involved in HCC development by regulating cell cycle progression and may be a promising target in the treatment of HCC.